2021
DOI: 10.1007/s12274-021-3293-3
|View full text |Cite
|
Sign up to set email alerts
|

Shining light on transition metal sulfides: New choices as highly efficient antibacterial agents

Abstract: Globally, millions of people die of microbial infection-related diseases every year. The more terrible situation is that due to the overuse of antibiotics, especially in developing countries, people are struggling to fight with the bacteria variation. The emergence of super-bacteria will be an intractable environmental and health hazard in the future unless novel bactericidal weapons are mounted. Consequently, it is critical to develop viable antibacterial approaches to sustain the prosperous development of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
56
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 209 publications
0
56
1
Order By: Relevance
“…Photothermal therapy (PTT) is a hot topic in recent years, which has a bactericidal mechanism completely different from traditional antibiotic treatment. [36][37][38] By combining near-infrared laser irradiation with a powerful light-absorbing material (such as graphene), light energy is converted into heat energy. In addition, unlike spherical, cube-shaped or rod-shaped nanomaterials, graphene nanosheets have a unique flexible two-dimensional structure and a large specific surface area, which ensures more efficient contact with bacterial cells or biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…Photothermal therapy (PTT) is a hot topic in recent years, which has a bactericidal mechanism completely different from traditional antibiotic treatment. [36][37][38] By combining near-infrared laser irradiation with a powerful light-absorbing material (such as graphene), light energy is converted into heat energy. In addition, unlike spherical, cube-shaped or rod-shaped nanomaterials, graphene nanosheets have a unique flexible two-dimensional structure and a large specific surface area, which ensures more efficient contact with bacterial cells or biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that transition metal sulfides with adjustable spectral characteristics and controlled morphology are very promising bactericidal agents capable of causing severe oxidative stress in bacteria under radiation [ 7 , 8 , 9 ]. At the same time, the development of methods for stabilizing nanoparticles is still relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Medical cotton gauze is widely used as a dressing material in the clinical treatment of skin wounds because of its excellent mechanical properties, good biocompatibility, and low cost. In addition, its porous structure and abundant hydrophilic groups on the surface make it outstanding in the moisture management of wounds. These two features, however, also create an ideal environment for the survival and growth of microorganisms such as many types of bacteria, which usually cause inflammation and excessive immune responses. Particularly, medical gauze used in hospitals is often exposed to a variety of super pathogenic bacteria caused by the extensive application of antibiotics, leading to severely delayed wound healing processes or even nonhealing wounds. Therefore, there is a strong demand to develop functional medical gauzes with broad-spectrum antibacterial and anti-inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%